The Effectiveness of Tobacco Control Interventions: A Literature Review and Comparative Analysis of India and the United Kingdom - Arrish, Mahdi (AlQalam Journal of Medical and Applied Sciences, 2025)
This study conducted a descriptive comparison between India (a developing country) and the United Kingdom (a developed country) to critically assess the efficacy of current tobacco control initiatives that may help lower smoking prevalence. This review found that the most effective tobacco control interventions are tobacco taxation and pricing, and the ban on smoking at workplaces and public places. However, these measures should be combined with other important interventions, such as brief interventions, banning tobacco advertising, regulating tobacco labelling and packaging, and raising awareness of the health hazards of tobacco, to bring about a substantial effect. According to this review, it appears that the UK has a superior status to India in the implementation of tobacco control programs.